MOBILE PHONE DEPENDENCY AND ITS IMPLICATIONS AMONG ARTS AND SCIENCE COLLEGE STUDENTS - DR.P.MOHANKUMAR; DR.P.UHAYASHANKAR; DR.C.SIVAGURUNATHAN (International Journal of Pharma and Bio Sciences, 2016)
This study aims to address possible association between over usage of mobile phones and their effect on health, psychology and social participation of individuals and groups. We have tried to find out how arts and science students use their mobile phones during college hours and off college hours and what effect this has left on their health. The method of the study focuses on mobile phone dependency of 150 arts and science students who use mobile phones for calls, messaging and for internet surfing and suing the social media on their mobile phones. Statistical analysis shows that there is acute dependency of the students on mobile phones with symptoms of sleeplessness and stress disorders, distraction and decrease in social interaction. The study has made an association between the critical aspects of health, psychology and social stress and over use of mobile phones. Further studies would be needed to find out the use of mobile phone by students which minimize the ill effects.